Biological Motion induced mu suppression is reduced in Early Psychosis (EP) patients with active negative symptoms and Autism Spectrum Disorders (ASD). (30th April 2016) - Minichino, Amedeo; Singh, Fiza; Pineda, Jaime; Friederich, Elisabeth; Cadenhead, Kristin S.
Abstract: There is evidence of genetic and neural system overlap in Autism Spectrum Disorder (ASD) and Early Psychosis (EP). Five datasets were pooled to compare mu suppression index (MSI), a proxy of mirror neuron activity, in EP, high functioning ASD, and healthy subjects (HS). ASDs and EPs with "active" negative symptoms showed significant differences in mu suppression, in response to Biological Motion/point-light display animation, compared to HS. Preliminary findings suggest that similar neural network deficits in ASD and EP could be driven by the expression of negative symptoms in the latter group of patients. These findings may aid future studies on EP and ASD and facilitate the formulation of new hypotheses regarding their pathophysiology. Highlights: We compared mu suppression index (MSI) in EP, ASD, and HS. EP and ASD showed MSI abnormalities in response to a Biological Motion animation. In the EP group, those with active negative symptoms had the most prominent deficits. This is the first study comparing MSI activity in patients with EP and ASD.